Oral Opportunistic Infections in Patient with HIV Wasting Syndrome - Mega Rafika; Tenny Setiani Dewi (Scientific Dental Journal, 2019)
Background: Human immunodeficiency virus (HIV) wasting syndrome is a condition in which weight loss, fever, and chronic diarrhea occur for more than 30 days without any causes other than HIV infection. HIV causes an immunocompromised condition resulting in susceptibility to infection. The opportunistic infections are oral candidiasis, herpes simplex virus (HSV), and tuberculosis. This study aims to explain oral opportunistic infections in a patient with wasting syndrome. Case Report: A 20-year-old female, who was 165 cm in height and 33.75 kg in weight, with wasting syndrome, pulmonary tuberculosis, oral candidiasis, and angular cheilitis was referred from an internist in Hasan Sadikin Hospital. Extraoral examination showed a yellowish brownish crust on the lips. Intraoral examination showed multiple ulcers covered by a yellowish membrane on the labial mucosa. The white plaques were scrapable, and an erythematous was found on the dorsum of the tongue, buccal mucosa, and palate. Laboratory results revealed a decrease in hemoglobin, hematocrit, leucocyte, erythrocyte, basophil, neutrophil, lymphocyte, albumin, reactive anti-HSV IgG, CD4 16 cell/µl, mycology culture test, chest x-ray, and sputum. On the basis of anamnesis, clinical features, and laboratory examination, the patient was diagnosed with stomatitis herpetica and oral candidiasis. Chlorhexidine gluconate 0.2%, nystatin oral suspension, vitamin B12, folic acid, and vaseline album were administered on the lips. Clinical recovery of oral candidiasis was accomplished after five weeks of therapy. Conclusion: Opportunistic infections in patient with wasting syndrome are oral candidiasis, herpetic stomatitis, and tuberculosis.